Egg morphology, laying behavior and record of the host plants of Ricania speculum (Walker, 1851), a new alien species for Europe (Hemiptera: Ricaniidae) - Rossi, Elisabetta; Stroiński, Adam; Lucchi, Andrea (Zootaxa, 2015)
The exotic planthopper, Ricania speculum (Ricaniidae) was recently detected in Liguria, in northern Italy, and recorded as a first alert for Europe. The first morphological description of eggs and laying behavior are given. Eggs are inserted into the woody tissue of a wide range of different host plants in such a unique manner among native and alien planthoppers of Italy that it can be used to describe the prevalence and diffusion of the species in new environments, though in the absence of juveniles and/or adults. In addition, the paper lists the host plants utilized for egg laying and describes the eggs.